Service Level Agreement (SLA) Chains Supported by Cloud in a Complex Port Ecosystem with Competing Stakeholder Goals: Editorial - C. Peoples; A. Moore; N. Georgalas (EAI Endorsed Transactions on Cloud Systems, 2022)
-